A comparative study of oral health attitudes and behavior using the Hiroshima University - Dental Behavioral Inventory (HU-DBI) between dental and civil engineering students in Colombia - Jaramillo, Jorge A. (2013)
The aim of this study was to use the Hiroshima University - Dental Behavioral Inventory (HU-DBI) to compare oral health attitudes and behavior of dental and civil engineering students in Colombia. The HU-DBI's survey consisting of twenty dichotomous responses (agree-disagree) regarding tooth brushing, was completed at University Antonio Narino for the dental students and the University of Cauca for the civil engineering students. The Spanish version of the HU-DBI questionnaire was taken by 182 of 247 dental students and 411 of 762 engineering students. The data was-statistically analyzed by the chi-square test and backward logistic regression. Compared to the engineering students, the dental students were more likely to agree with questions such as “I am bothered by the color of my gums”(OR = 2.2, 95% CI: 1.3-3.7),“I think I can clean my teeth well without using toothpaste” (OR = 3.0, 95% CI: 1.5-5.9), “I have used a dye to see how clean my teeth are” (OR = 2.9, 95% CI: 1.9-4.3), and “I have had my dentist tell me that I brush very well” (OR = 2.0, 95% CI: 1.3-3.1). The dental education curriculum in a dental school compared to a civil engineering school in Colombia indicated that a three-phase curriculum in didactics and clinics increased oral health attitudes and behavior from entry to graduation.